Penggunaan Sosial Media dalam Upaya Penolakan Pembagian Konsesi Tambang Pada Ormas Agama: Studi Kasus Muhammadiyah dan Nahdlatul Ulama - Sutan, Arissy Jorgi; Al Kausar, Jefri; Sazeta, Mirza; Hanafi Ahmad, Zakly; Romadhon, Aditya; Pratama, Galank (Jurnal Agregasi, 2025)
This study examines social media as a platform for rejecting mining concessions by Nahdlatul Ulama and Muhammadiyah. Using a qualitative case study approach and Nvivo 12 Plus for analysis, it draws data from Twitter/X. The findings reveal differing protest focuses: criticism of Muhammadiyah highlights its reputation, while protests against Nahdlatul Ulama emphasize concession acceptance. Social media amplifies voices broadly, playing a key role in modern protests. Popular narratives mainly center on mining, with some also scrutinizing Muhammadiyah. A significant wave of rejection emerged, with strong negative reactions from netizens. This study has limitations in focusing data on social media platforms such as Twitter/X. Recommendations for further research can focus on environmental issues and Indigenous communities in the frame of protests through social media.